One-pot reactions in the synthesis of thiazolidinone derivatives by nano-Fe3O4–cysteine catalyst. (2nd November 2022) - Hajighasemi, Halimeh; Foroughifar, Naser; Khajeh-Amiri, Alireza; Balali, Ebrahim
Abstract : A simple and efﬁcient one-pot approach for assembling some benzylidene-2-(benzo[ d ]thiazol-2-ylimino) thiazolidin-4-one derivatives utilizing Fe3 O4 –cysteine as an efficient catalyst via reaction between benzo[ d ]thiazol-2-amine, ammonium thiocyanate, chloroacetyl chloride, and aromatic aldehydes, in EtOH at 80°C, is reported. Minimize chemical waste, time-saving, simplify practical aspects besides the good functional group tolerance and easy separation of the nano-catalyst are the prominent features of the present methodology. In vitro antibacterial screening of synthesized compounds against Staphylococcus aureus ATCC 25923, Staphylococcus epidermidis ATCC 1446, Bacillus cereus ATCC 1247, Escherichia coli ATCC 1399, and Pseudomonas aeruginosa ATCC 1430 in different concentrations of the samples (200, 100, 50, 25, 12.5, 5.25, and 3.12 µg/ml) was done, and the lowest minimum inhibitory concentration, minimum bactericidal concentration, the zone inhibitory were measured, and biofilm formation was investigated. GRAPHICAL ABSTRACT: UF0001